Jesus remembered - Dunn, James D. G., 1939- (Grand Rapids, Mich. : W.B. Eerdmans Pub., 2003)
Focusing on Jesus, this first volume has several distinct features. It garners the lessons to be learned from the "quest for the historical Jesus" and meets the hermeneutical challenges to a historical and theological assessment of the Jesus tradition. It provides a fresh perspective both on the impact made by Jesus and on the traditions about Jesus as oral tradition, hence the title "Jesus Remembered." And it offers a fresh analysis of the details of that tradition, emphasizing its characteristic (rather than dissimilar) features. Noteworthy too are Dunn's treatments of the source question (particularly Q and the noncanonical Gospels) and of Jesus the Jew in his Galilean context.
Christianity in the making -- pt. 1. Faith and the historical Jesus. Introduction -- The (re- )awakening of historical awareness -- The flight from dogma -- The flight from history -- History, hermeneutics and faith -- pt. 2. From the Gospels to Jesus. The sources -- The tradition -- The historical context -- Through the gospels to Jesus -- pt. 3. The mission of Jesus. Beginning from the baptism of John -- The kingdom of God -- For whom did Jesus intend his message? -- The character of discipleship -- pt. 4. The question of Jesus' self-understanding. Who did they think Jesus was? -- How did Jesus see his own role? -- pt. 5. The climax of Jesus' mission. Crucifixus sub Pontio Pilato -- Et Resurrexit -- Jesus remembered.
Includes bibliographical references (p. 901-948) and indexes.
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- History of doctrines -- Early church, ca. 30-600.